2020
DOI: 10.16986/huje.2020063670
|View full text |Cite
|
Sign up to set email alerts
|

Students Experiences on Using an Authentication and Authorship Checking System in E-Assessment

Abstract: Bu çalışmanın amacı, e-değerlendirme sürecinde kimlik doğrulama ve yazarlık kontrol sistemi kullanımında öğrencilerin deneyimlerini belirlemektir. Çalışma, Avrupa Komisyonu tarafından finanse edilen Horizon 2020 projesi kapsamında geliştirilen TeSLA Projesi (Öğrenme için Uyarlanabilir Güvene dayalı bir e-Değerlendirme Sistemi) kapsamında gerçekleştirilmiştir. TeSLA sistemi, e-değerlendirmede kimlik doğrulama, yüz tanıma, ses tanıma, tuş vuruşu dinamikleri, yazarlık kontrolü ve intihal araçları gibi çeşitli ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The literature review revealed similar findings related to this theme. For example, cheating, plagiarism, and academic dishonesty were the major challenges of instructors in online assessment (Guangul et al, 2020;Guerrero-Roldán et al, 2020;Hussein et al, 2020;Kocdar et al, 2018;Kundu & Bej, 2021). Instructors should find appropriate solutions to the dishonest behaviors of students and some solutions addressed by the instructors in the current study were in line with the literature such as increasing the number and diversity of question types and minimizing the exam duration (Peterson, 2019).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The literature review revealed similar findings related to this theme. For example, cheating, plagiarism, and academic dishonesty were the major challenges of instructors in online assessment (Guangul et al, 2020;Guerrero-Roldán et al, 2020;Hussein et al, 2020;Kocdar et al, 2018;Kundu & Bej, 2021). Instructors should find appropriate solutions to the dishonest behaviors of students and some solutions addressed by the instructors in the current study were in line with the literature such as increasing the number and diversity of question types and minimizing the exam duration (Peterson, 2019).…”
Section: Discussionmentioning
confidence: 59%
“…Using appropriate assessment methods, such as take-home exams or authentic tasks, was also recommended to prevent dishonest behaviors (Şenel & Şenel, 2021b). There were also various technical solutions to ensure reliability in assessments, such as using online proctoring tools (Hussein et al, 2020), authentication tools for checking the identity of learners (Okada et al, 2019), and authorship tools for verifying the originality of the documents (Guerrero-Roldán et al, 2020). Continuous assessment in which students are assessed via small quizzes for overall times could be a good solution for security (Doğan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the operating conditions include the commitment of involved stakeholders, as well as the participation of students; for example, in the preparation of questions [54,55]. Undoubtedly, the educator has an important role to play in providing the conditions for e-assessment.…”
Section: Conditions and Suggestionsmentioning
confidence: 99%
“…This review of the literature indicates the qualities necessary for an educator, i.e., to be flexible and open [60]. First of all, educators provide the process itself, administrative transactions and examinations [56], which include ensuring authorship and authentication; collecting results; and maintaining safe user data [54,59,61]. Regarding the security conditions, it is worth mentioning secure web browser availability and error recognition [53,61].…”
Section: Conditions and Suggestionsmentioning
confidence: 99%